Risiko Keamanan Pangan pada Makanan Homemade Sehat: Narrative Review - Amalia Akita; Gunawan, Roni; Daryana, Aditiya Pratama; Herkules Herkules; Pratama, Muchti Yuda (Journal of Educational Innovation and Public Health, 2026)
Homemade food is increasingly dominating the choices of consumers who are oriented towards a healthy lifestyle. However, the belief that self-cooking is synonymous with food safety is not always supported by scientific evidence. This Narrative Review aims to build an in-depth thematic synthesis of the various dimensions of food safety risks that arise in the process of preparing healthy homemade food, ranging from biological and chemical contamination, to human behavioral factors as the main agents of contamination. The study was conducted against seven reputable sources of scientific literature published between 2010–2025, including observational, experimental, cross-sectional, and review studies. Four main themes were identified: (1) risky behaviors in the household kitchen as the dominant factor; (2) unexpected cross-contamination pathways including table salt as a vector; (3) chemical and biological contaminants hidden in "healthy" materials; and (4) evidence-based interventions that have been proven to be effective. This review confirms that homemade food safety is a behavioral issue, not just a technical one, so the intervention approach must be multidimensional and sustainable.